Alfabetização científica no contexto escolar: uma análise desse processo no nono ano do ensino fundamental - Viana, Sandra Franklin Rocha (Universidade Federal do Tocantins, 2022)
This research investigated the process of Scientific Literacy (SL) in the ninth grade of Elementary School of Tocantins public school. From an interdisciplinary perspective, it was sought to understand the teaching of Geography and Natural Sciences from the environmental point of view of the school community. The exploratory case study method was used in two schools in Palmas during the school year of 2016. Data were generated from individual intensive interviews, focus group, documentary research, direct and participatory observation, seminar, field records and written texts, whose actors were: management team, teachers and students. The focus was the interactive discussion between teachers and students during the Didactic Sequences (DS). These were interpreted through content analysis, observing the frequency in which the phenomenon occurred. The result shows the existence of some elements of SL in the teaching process of the two disciplines studied. We define Scientific Literacy as the set of teaching practices that promote the understanding of scientific languages, expanding knowledge for new languages, giving the individual's learning and interpretation about the world and the locality in which they live. Environmental education is addressed as a mere curricular component, while scientific education is not contemplated in this context; Interdisciplinarity remains in related areas without breaking the disciplinary boundaries of dialogue; and continuing education does not meet this contemporary perspective. Therefore, it is necessary to implement a SL project in basic education that combines the skills, competences and learning expectations of the diversified part of the curriculum, especially to apply the theoretical, practical and systematized procedures of modern science and technology.